Interdisciplinary applications of the person-centered approach - Motschnig-Pitrik, Renate; Lux, Michael; Cornelius-White, Jeffrey H. D. (Springer New York, 2013)
The hallmark of Carl Rogers' work, the Person-Centered Approach (PCA), has long had a major impact on psychological research and clinical practice. Currently, as more diverse professionals recognize the relevance of humanistic thought to their fields, it is enjoying a wider diversity of applications across disciplines, populations, and settings. Interdisciplinary Applications of the Person-Centered Approach unfolds client-centered concepts into real-world contexts. The versatility and power of person-centered practice are on full display in an engaging integrative framework, featuring extended examples, practical guidelines, and graphic concept maps. Renowned scholar-practitioners illustrate innovative applications as diverse as motivational interviewing, parent training, learner-centered instruction, and peace negotiations to promote cross-disciplinary dialogue and collaboration, and potentially to solve larger societal problems. Support for the PCA spans a variety of areas including: • Clinical applications in psychotherapy and medicine. • Education, including elementary, higher, adult, and e-learning. • Child, family, and lifespan studies. • Business, management, leadership, and coaching. • Conflict resolution and constructive communication. Interdisciplinary Applications of the Person-Centered Approach complements its companion volume, Interdisciplinary Handbook of the Person-Centered Approach: Research and Theory, by enlightening researchers and practitioners who want to broaden their academic and clinical horizons. Both are significant resources for researchers in a variety of sciences, such as psychology, neuroscience, therapy, education, communication, and medicine, and for students of humanistic psychology.